1996
DOI: 10.7863/jum.1996.15.6.441
|View full text |Cite
|
Sign up to set email alerts
|

Translabial ultrasonography and placenta previa: does measurement of the os-placenta distance predict outcome?

Abstract: The aim of this study was to assess the value of the measurement of os-placenta distance by translabial ultrasonography in the evaluation of placenta previa. This method was used in 40 women with suspected placenta previa to measure the distance between the placenta and internal cervical os. Sonographic diagnoses were compared to placental location determined at delivery. Translabial ultrasonography proved superior to the transabdominal route in both diagnosis and exclusion of placenta previa. Measurement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 3 publications
3
37
0
Order By: Relevance
“…This technique is used in many clinics to visualize the cervix and to assess placental location. 17,18,21,22 The cases reported here confirm that transperineal sonography can successfully visualize blood vessels crossing the cervical os in cases of vasa previa. Confirmation that the structures crossing the os are blood vessels can be obtained with Doppler evaluation in this transperineal perspective.…”
supporting
confidence: 57%
“…This technique is used in many clinics to visualize the cervix and to assess placental location. 17,18,21,22 The cases reported here confirm that transperineal sonography can successfully visualize blood vessels crossing the cervical os in cases of vasa previa. Confirmation that the structures crossing the os are blood vessels can be obtained with Doppler evaluation in this transperineal perspective.…”
supporting
confidence: 57%
“…As compared to those with cervical os to placental edge distance between 11-20 mm, patients with internal cervical os to placental edge distance 10 mm have high rates of antepartum hemorrhage (29% vs 3%; odds ratio, 11.5; 95% confidence interval, 1.6e76.7) 13 and cesarean delivery rates 73-91% vs 24-40%. 10,13,14 However, there are no significant differences in the gestational ages at delivery between the 2 groups and 75-80% of these patients are delivered at term. 13 The thickness of the lower placental edge has also been evaluated as a predictor of bleeding in patients with marginal/low-lying placentas.…”
Section: Marginal/low-lying Placentamentioning
confidence: 75%
“…20 In women with low-lying placenta (cervical os to placental edge distance 20 mm), cervical length has been studied as a predictor of antepartum bleeding and indicated preterm birth. 10,[12][13][14] It was found that short cervix ( 25 mm) was associated with higher rates of antepartum bleeding (75% vs 31%; P ¼ .02), blood transfusion (25% vs 3%; P ¼ .02), lower birthweight (62% vs 17%; P ¼ .02), and neonatal intensive care unit admissions (50% vs 17%; P ¼ .04). 22 Figure 3 is a proposed guideline for managing asymptomatic patients with marginal or low-lying placenta based on published literature that has used internal cervical os to placental edge distance cutoffs of <1, 1-2, and >2 cm; placental edge thickness cutoff of 1 cm; and cervical length cutoff of 25 mm.…”
Section: Marginal/low-lying Placentamentioning
confidence: 95%
See 1 more Smart Citation
“…Transperineal or translabial ultrasound (using a transabdominal probe) can also improve upon the diagnostic accuracy of TAS and may be a useful alternative when TVS is not available [29].…”
Section: Prediction Of Placenta Previa At Deliverymentioning
confidence: 99%